Resolusi Konflik dalam Perspektif Nilai-Nilai Kristen: Analisis Kepemimpinan Toxic dan Narsis pada Lembaga Pendidikan Kristen - Kurniawan, Garry; Ibelala Gea (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze toxic and narcissistic leadership in Christian educational institutions. The research method employed is a literature review with a content analysis approach. Data were collected through documentation studies of various academic books and relevant scholarly journals, then systematically analyzed to identify themes, patterns, and strategic insights. This literature review seeks to provide an in-depth understanding of toxic and narcissistic leadership phenomena, focusing on the influencing factors, their implications for organizations, and potential conflict resolution strategies. The findings reveal that toxic and narcissistic leadership has a negative impact on organizational health, particularly within Christian education, which should uphold the values of love, sacrifice, and service. Conversely, the implementation of conflict resolution based on Christian values can restore relationships, strengthen leadership integrity, and foster a healthy organizational culture. This study emphasizes the importance of transforming toxic and narcissistic leadership into leadership grounded in the values of Christ so that Christian educational institutions can remain consistent with their mission to educate, guide, and serve with love.